THE DEVELOPMENT OF SILOMPEK TRADITIONAL GAME AS AN INTEGRATED THEMATIC LEARNING MEDIA IN CHARACTER-BASED LEARNING IN THE PRIMARY SCHOOL - Utama, David Pra; Amri, Andi; Tae, Lidwina Felisima (Indonesian Journal of Educational Assessment, 2021)
The success of learning with the application of 2013 Curriculum is supported by the availability of integrated thematic learning media. However, the availability of such media is one of the inhibiting factors in realizing the quality ofeducation, especially in primary school education. This research is motivated by the lack of integrated thematic learning media in 2013 Curriculum in realizing a character-based education. The purpose of this research is to develop an integrated thematic learning media in 2013 Curriculum which can increase creativity, innovation, communication skills, collaboration, and self-confidence of elementary school students by implementing a traditional game in West Sumatra province. This research is a development research using the ADDIE method. The subjects of this study were 25 students and 2 teachers. The results of this study indicated that the development of Silompek learning media can increase creativity, innovation, communication skills, collaboration, and self-confidence as the characters in learning for elementary school students. The implication of this research is that the media developed can be used by elementary school teachers in 2013 curriculum